Fostering responsible innovation with critical design methods - Alexi Orchard; Marcel O’Gorman (Journal of Responsible Innovation)
In light of increasingly harmful social, psychological, and environmental impacts stemming from the tech industry, this article contributes to ongoing conversations regarding the need for more rigorous ethical deliberation in the engineering design workflow. We present two examples of pedagogical interventions dedicated to injecting critical design methods into the education of future tech developers to help foster responsible innovation: 1) a cross-disciplinary curricular intervention with English and Systems Design Engineering students; 2) a series of Responsible Innovation workshops conducted with students. Critical design, an arts-based research practice that resists unreflective technological progress, is uniquely situated to enhance current approaches in engineering ethics curricula by creating space for reflection about and design-based responses to the impacts of tech innovation. We argue that methods and expertise from the arts and humanities – disciplines that excel in the critical contextualization of technological progress – can help foster an ethos of responsible innovation in engineering education.